αvβ6-integrin targeted PET/CT imaging in pancreatic cancer patients using 68Ga-Trivehexin - Rehm, Jana; Winzer, Robert; Pretze, Marc; Müller, Juliane; Notni, Johannes; Hempel, Sebastian; Distler, Marius; Folprecht, Gunnar; Kotzerke, Jörg (Frontiers in Nuclear Medicine, 2024)
Purpose 68Ga-Trivehexin is a PET tracer targeting αvβ6-integrin, a transmembrane receptor that is frequently expressed by pancreatic cancer cells. This study aimed to determine the biokinetics, image contrast, and acquisition parameters for 68Ga-Trivehexin PET imaging in pancreatic cancers. Methods 44 patients with pancreatic cancer underwent Trivehexin PET/CT between June 2021 and November 2022 (EK-242052023). Biokinetics and -distribution were extracted. Previous imaging follow-up imaging, and histological findings were used as reference standards. A one-way ANOVA test, followed by Tukey HSD post-hoc test was conducted. T-tests for subgroups ± chemotherapy prior to PET were performed. Based on dynamic PET data (n = 11) recorded over 45 min, time-activity curves were generated. Results 68Ga-Trivehexin PET/CT detected 40 pancreatic cancers, SUVmax 12.6; range [5.1–30.8]; 39 liver metastases, SUVmax 7.9 [2.7–16.3]; 21 lymph node metastases, SUVmax 8.6 [2.5–15.0]; 17 peritoneal metastases, SUVmax 9.5 [4.0–16.9] and 14 other metastases, SUVmax 7.2 [2.9–13.1]. Tukey post-hoc analysis revealed significant differences for SUVmax in pancreatic cancer compared to SUVmax in liver metastases [4.74, 95%-CI (1.74, 7.75)], for SUVmax in pancreatic cancer to SUVmax in lymph node metastasis [4.07, 95%-CI (0.47, 7. 67)], for tumor-to-liver ratio (TLR) of liver metastasis to TLR of pancreatic cancer [1.82, 95%-CI (0.83, 2.80)], for TLR of pancreatic cancer to TLR of peritoneal carcinomatoses [−1.88, 95%-CI (−3.15, −0.61)], and TLR of pancreatic cancer to TLR of pleural carcinomatosis [−2.79, 95%-CI (−5.42, −0.18)]. When comparing subgroups ± chemotherapy prior to PET, TLR of pancreatic cancers and TLR of peritoneal carcinomatoses were significantly different. At 45 min p.i., the highest tumor-to-backround (TBR) was observed. Conclusion 68Ga-Trivehexin is suitable for imaging of αvβ6-integrin expression in pancreatic cancer due to its ability to distinguish primary carcinoma and metastases from background tissue.